Characterisation of heat-responsive novel miRNAs in wheat identified based on miRNome analysis - Kumar, Mahesh; Ranjeet R. Kumar; Jyoti P. Singh; Kajal Arora (Annals of Arid Zone, 2025)
MicroRNAs function as primary regulators of plant growth and development. RNA-RNA interaction plays a crucial role in gene regulation. The miRNA regulates the expression of functional genes related to plant development and other physiological processes. Under stressful conditions, the expression of most miRNAs that play a role in plant growth and development undergoes significant changes. Here, we identified nineteen heat-responsive novel miRNAs using the reference genome of Sorghum bicolor and Zea mays. The novel miRNAs genes were validated in four contrasting wheat cultivars - BT Schomburgk, PBW 343 (thermosusceptible) and HD 3086, Raj 3765 (thermotolerant) under heat stress (HS) treated conditions during the seedling stage by quantitative real-time PCR. Almost all the novel miRNAs showed significant downregulation in all the wheat cultivars under heat stress. We have cloned and characterised candidate 2233 miRNA from HD 3086. Secondary structure prediction and energy dot plot analysis showed very high stability of the identified novel miRNAs. Most of the identified targets of miRNAs were associated with stress-responsive genes and heat shock proteins. A negative correlation was seen between microRNAs (miRNAs) and their target genes. These identified novel miRNAs can be used for the development of ‘climate-smart’ wheat crops.